Susu Ibu Sebagai Inspirasi Dalam Penciptaan Karya Seni Patung - Kresna Yoga, I Gede Deva; Jodog, I Made; Setem , I Wayan (Program Studi Seni Murni ISI Bali, 2022)
Breastfeeding is the process of giving milk to a baby or child with breast milk form the mother’s breast. Through the breastfeeding process, there is a personal relationship between mother and child in loving energy. Various perspective on breastfeeding occur in the community, including knowledge about the importance of breastfeeding. The concept of breastfeeding, breastfeeding attitudes, visuals of the breastfeeding process are interesting thing to research and the serve as the basis for creating ideas. This creation aims to remind the importance of breastfeeding and increase knowledge and the creation of sculptures. The analysis is carried out based on aesthetic, semiotic and deformation theories. The research was conducted by means of observation, interviews, documentation and stages of creation with exploration, experimentation and formation. Utilization of the element and principles of sculpture is the basis of creation. The main media used are cornice and banana trees. As a form of creation are sculpture entitled “Mother’s Milk” and “ Mother’s Happiness”.